AutoCAD 2019 3D modeling - Hamad, Munir M. (Mercury Learning and Information, 2019)
"This book provides new and seasoned users with step-by-step procedures on creating and modifying 3D models, working with cameras and lights, assigning materials to objects, rendering, and printing. Unlike many AutoCAD competitors, it uses both metric and imperial units to illustrate the myriad tools for this popular application. Use the companion disc to set up drawing exercises and projects and see all of the book's figures including color. AutoCAD 2019 3DModeling includes 50 "mini-workshops," that complete small projects from concept through actual plotting. Solving all of the workshops will simulate the creation of full projects (architectural and mechanical) from beginning to end, without overlooking any of the basic commands and functions in AutoCAD 2019"--Back cover.